The Role of Innovation Capabilities in Improving MSME Performance: A Case Study of Pujorahayu Tourism Village - Helmita (LifeSciFi, 2025)
The transformation of the digital economy and the increasing intensity of global competition pose significant challenges for Micro, Small, and Medium Enterprises (MSMEs) in maintaining sustainable performance, especially in the rural tourism sector which often operates with a traditional business approach. This study aims to investigate the role of innovation capability as a strategic determinant in improving the performance of MSMEs in Pujorahayu Tourism Village. Using a qualitative approach with the systematic literature review method, data was collected and analyzed from various academic sources, industry publications, and policy documents during the period 2018–2024. The analysis is focused on three main dimensions of innovation capabilities: technological innovation, process innovation, and organizational innovation. The results of the study show that innovation capabilities play a critical role as a critical determinant in increasing revenue, market expansion, and operational efficiency of MSMEs in tourist villages, with the main mechanisms being resource optimization, creation of competitive advantages, and adaptation to market changes. These findings reinforce the relevance of Resource-Based View and Dynamic Capabilities Theory in the context of community-based tourism, as well as provide practical implications for the development of sustainable and locally-based MSME strategies.